2020
DOI: 10.3390/w12020446
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Magnetic Magnetite Nanoparticle for Coexistent Cr(VI) and Cu(II) in Mixed Solution

Abstract: The adsorption properties of coexistent Cr(VI) and Cu(II) in mixed solution on magnetic magnetite (Fe3O4) nanoparticle were studied in batch experiments. The influences of various factors, such as pH, adsorbent dose, temperature, initial concentration of metal ions, and coexisting ions in water were investigated. At the same time, the adsorption kinetics and adsorption isotherms were studied. The mechanism of adsorption for Cr(VI) and Cu(II) was investigated through the study of surface properties of Fe3O4, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 31 publications
8
44
0
2
Order By: Relevance
“…1b). This result is in agreement with (Zhang et al, 2020) who found that the isoelectric point (pH pzc ) value was between (3.0 -4.0). In an aqueous system, the surface of iron oxides is covered with groups of -FeOH, etc.…”
Section: Results and Discussion 1 Characterization 11 Point Of Zersupporting
confidence: 93%
“…1b). This result is in agreement with (Zhang et al, 2020) who found that the isoelectric point (pH pzc ) value was between (3.0 -4.0). In an aqueous system, the surface of iron oxides is covered with groups of -FeOH, etc.…”
Section: Results and Discussion 1 Characterization 11 Point Of Zersupporting
confidence: 93%
“…Magnetite atau Fe3O4 merupakan salahsatu nanopartikel yang banyak disintesis untuk berbagai aplikasi [3] . Sifat ferromagnetik dari magnetit telah banyak dimanfaatkan sebagai adsorben dalam mengadsorpsi kation-kation logam dari limbah cair [4] .…”
Section: Pendahuluanunclassified
“…It is evident that the distribution of Co on the biomass surface is closely associated with almost all Fe 3 O 4 aggregates (Fe and O-rich regions on elemental maps, Figure 8 ), indicating that the synergistic interactions with Fe 3 O 4 lead to the higher adsorption capacity of Co 2+ ions by the magnetic biosorbent. In aqueous solutions, −FeOH groups are present on iron oxide surfaces, and depending on the solution pH, they protonate or deprotonate to FeOH 2 + and FeO − [ 40 ]. With the increase in the solution pH, FeO − increased, facilitating the removal of Co 2+ by electrostatic adsorption [ 10 , 25 ].…”
Section: Resultsmentioning
confidence: 99%